Comparative Extraction of Phenolic Compounds from Olive Leaves Using a Sonotrode and an Ultrasonic Bath and the Evaluation of Both Antioxidant and Antimicrobial Activity - Beatriz Martín-García; Soumi De Montijo-Prieto; Maria Jiménez-Valera; Alegría Carrasco-Pancorbo; Alfonso Ruiz-Bravo; Vito Verardo; Ana María Gómez-Caravaca (MDPI AG, 2022)
A sonotrode ultrasound-assisted extraction of phenolic compounds from olive leaves has been developed using a Box-Behnken design to optimize the effects of solvent composition and ultrasound parameters. The determination of single phenolic compounds was performed by HPLC-MS and the highest recovery in total compounds, oleuropein and hydroxytyrosol was achieved using EtOH/H2O (55:45, v/v), 8 min and 100% of amplitude. The optimal conditions were applied on leaves from seven olive cultivars grown under the same conditions and the results were compared with those found by using a conventional ultrasonic bath, obtaining no statistical differences. Moreover, antioxidant activity by FRAP, DPPH and ABTS in these olive leaf extracts was evaluated and they exhibited a significant correlation with oleuropein and total phenolic content. All cultivars of olive leaf extracts were found to be active against S. aureus and methicillin-resistant S. aureus with minimum bactericidal concentration (MBC) values) that ranged from 5.5 to 22.5 mg mL−1. No extracts showed antimicrobial activity against C. albicans. The percentages of mycelium reduction in B. cinerea ranged from 2.2 and 18.1%. Therefore, sonotrode could be considered as an efficient and fast extraction technique that could be easily scaled-up at industrial level, thus allowing for olive leaves to be revalorized.